Analisis Pengaruh Corporate Governance dan Kinerja Keuangan terhadap Pengungkapan Islamic Social Reporting pada Perusahaan Perbankan Syariah Periode 2017-2021. - Nasrulloh, Muchammad Chamdan; Pranjoto, Gatot Heru (Management Department of Economics and Business Of Trunojoyo Madura University, 2023)
The purpose of this study is to find out whether the Corporate Governance and Financial Performance variables have a partial or simultaneous effect on the disclosure of Islamic Social Reporting in Islamic banking companies in Indonesia for the 2017-2021 period. This research was conducted in a quantitative descriptive manner using secondary data obtained from the financial reports of the Indonesia Stock Exchange (IDX) and the Financial Services Authority (OJK). The population selected in this study were 12 banking companies, the sample was selected using a purposive sampling method and 10 companies met the criteria. The variables used in this study are the board of commissioners, audit committee, DER and ROA as independent variables, Islamic Social Reporting (ISR) as the dependent variable. Hypothesis testing in this study used the t test (partial), F test (simultaneous) with the SPSS (statistical product and service solutions) application tool. The results of this study prove that: (1) The results of testing the analysis of corporate governance with indicators of the board of commissioners have a positive but not significant effect and the audit committee has a negative but not significant effect on disclosure of Islamic Social Reporting (ISR) (2) The results of testing analysis of financial performance which include indicators DER and ROA show that financial performance variables have a positive but not significant effect on disclosure of Islamic Social Reporting (ISR) (3) From the simultaneous test results, the results show that the Board of Commissioners, Audit Committee, DER and ROA simultaneously have a significant influence on Islamic Social Disclosure Reporting (ISR).